Mudança curricular e a construção do conhecimento pedagógico do conteúdo na educação física - Jardim, Juliana Gomes [UNESP]; Betti, Mauro [UNESP] (My University, 2014)
To understand how teachers deal with curriculum change proposals, and how their professional knowledge are involved in this process, is critical in order to understand the impact of these changes in pedagogical practice. From L. S. Shulman’s typology of teacher knowledge, we aimed to describe and interpret how a Physical Education teacher deals with the pedagogical content knowledge when developing a theme from Curriculum Proposal of Physical Education from the State of São Paulo (PPC-EF). A case study was conducted with the use of semi-structured interviews and classroom observation. The teacher made adjustments at the approach and activities suggested by the PPC-PE, mobilizing several teacher knowledge, and her autonomy was not removed. On the other hand, difficulties in relating “theory” and “practice” indicate the need for construction of pedagogical content knowledge to better direct the learning of students to the critical appropriation of movement culture.

Compreender como os professores lidam com propostas de mudança curricular e como seus saberes profissionais intervêm nesse processo é fundamental para entender o impacto dessas mudanças na prática pedagógica. Com base na tipologia de saberes docentes de L. S. Shulman, objetivou-se descrever e interpretar como uma professora de Educação Física lida com o conhecimento pedagógico do conteúdo no desenvolvimento de um tema da Proposta Curricular de Educação Física do Estado de São Paulo (PPC-EF). Realizou-se um estudo de caso que se valeu de entrevistas semiestruturadas e observação de aulas. A professora realizou adaptações na abordagem e nas atividades sugeridas pela PPC-EF, mobilizando saberes docentes diversos, sem que isso eliminasse a sua autonomia. Já as dificuldades em relacionar “teoria” e “prática” indicam a necessidade de construção do conhecimento pedagógico do conteúdo que melhor direcione a aprendizagem dos alunos para a apropriação crítica da cultura de movimento.
Curriculum change and the building of pedagogical content knowledge in physical education
Keywords: Physical education; Pedagogical content knowledge; Curriculum; Educacao Fisica Escolar; Conhecimento pedagógico do conteúdo; Curriculo